Persepsi Guru PAI tentang Pentingnya Pendidikan Karakter dalam Pembelajaran di SMP Swasta Islam Proyek UISU Siantar - Dewi Kirana (STAI UISU Pematangsiantar, 2022)
This study aims to explore the perceptions of Islamic Religious Education (PAI) teachers regarding the importance of character education in learning at SMP Swasta Islam Proyek UISU Siantar. Using a descriptive qualitative method, in-depth interviews and observations were conducted with two PAI teachers to understand how they integrate character values into daily learning activities. The findings show that both PAI teachers have a positive view of character education, considering it an integral part of Islamic education. However, they also face challenges such as limited time and suboptimal parental support. This study recommends enhancing collaboration between teachers, schools, and parents to strengthen students' character education.